Spontaneous Colonic Perforation in a Four-Month-Old Infant: A Rare Case Report - Zaky Davidia Rifaldi; Galih Widiyanto (International Journal Labs, 2025)
Spontaneous colonic perforation is a rare clinical entity in infants beyond the neonatal period, generally classified into stercoral and idiopathic types, with the latter being sporadic and challenging to diagnose due to nonspecific presentations. We report the case of a five-month-old female infant, born preterm at 36 weeks and 6 days, who presented with progressive abdominal distension, absence of stool and flatus, and clinical signs of peritonitis. Exploratory laparotomy revealed a laceration-type perforation extending from the left transverse to descending colon with surrounding necrosis, without any history of trauma or abdominal procedures, supporting an idiopathic etiology. Surgical management included resection of the affected segment with end-to-end anastomosis and ileostomy, while laboratory findings demonstrated anemia, hypocalcemia, mild hyperglycemia, and leukocytosis. This case emphasizes the importance of early recognition of spontaneous colonic perforation in infants, as delayed intervention is associated with high morbidity and mortality, and highlights the need for prompt surgical management to improve outcomes in this rare but life-threatening condition.